Performance and operation strategy optimization of a new dual-source building energy supply system with heat pumps and energy storage. (1st July 2021) - Wang, Yubo; Quan, Zhenhua; Jing, Heran; Wang, Lincheng; Zhao, Yaohua
Highlights: A new dual-source building energy supply system was proposed. Load-forecasting and system performance models were established based on big data. The optimal operation strategy was proposed and verified through simulation. The new system has evident advantages in economy and energy saving. Abstract: The use of renewable energy is an important technical way to achieve building energy conservation and environmental protection. In this study, a new type of dual-source building energy supply system with heat pumps and energy storage, which can solve the problems of unstable operation and low reliability of a single-energy system and high investment and operation cost of existing multi-source energy systems, is proposed. In this system, photovoltaic–thermal water is used as the low-temperature heat source of the water source heat pump and the air source heat pump as the auxiliary energy supply device to realize cascade utilization of energy. "Peak load shifting" and minimization of building energy consumption and operation costs are realized by storing energy (cold and heat) at night when electricity prices are low. On the basis of the long-term monitoring data of the energy supply system for an office building, load-forecasting and system performance models are established, and the operation strategy in winter and summer is optimized. Then, the whole-year operation of the system is simulated and analyzed. Results show that the optimized system runs efficiently and can save approximately 10% of operating costs compared with the situation before optimization. The operating cost of the system is 55% of that of the conventional air source heat pump system, and its dynamic payback period is 3.66 years. The proposed system is a form of building energy supply system worthy of popularization and application in cold regions.